Comparative Study of the Elements of Qulubun Ya'qilun and Qulubun La Yafqahun in Qs. Al-A'raf Verse 179 And Al-Hajj Verse 46 - Abror, M.Qusyairi; Sassi, Komarudin (West Science Islamic Studies, 2025)
This research aims to examine and compare the elements contained in the phrases "Qulubun Ya'qilun" and "Qulubun La Yafqahun" found in Surah Al-A'raf, verse 179, and Surah Al-Hajj, verse 46. Both phrases describe the condition of the human heart in understanding divine revelation and the signs of Allah's greatness. The research method used is a textual exegesis study and Arabic linguistic analysis to deeply explore the meaning of words and the context of the verses. The analysis results indicate that "Qulubun Ya'qilun" refers to a heart capable of understanding, contemplating, and learning from Allah's verses, thereby opening itself to receiving guidance and wisdom. Conversely, "Qulubun La Yafqahun" describes a closed heart, unable to grasp meaning, and unwilling to accept the truth, leading to ignorance and hardness of heart. This study emphasizes the importance of the spiritual condition of the heart in the process of understanding revelation and contributes to the fields of exegesis and Islamic psychology. This research also opens new insights into how different heart conditions affect human attitudes and behavior in religious life.